Surgical Treatment of Enormous Recurrent Dermatofibrosarcoma Protuberans - Xing, Shijie; Wang, Jianjun; Zhai, Wei; Xia, Tian; Wang, Chuanxiao (The Thoracic and Cardiovascular Surgeon Reports, 2015)
A patient with enormous recurrent dermatofibrosarcoma protuberans underwent modified three-dimensional histology surgery. Frozen-section examination was used to identify the margins. The patient had a normal postoperative course.
Keywords: chest wall; tumor; surgery/incisions